2021
DOI: 10.47162/rjme.61.3.06
|View full text |Cite
|
Sign up to set email alerts
|

Medullary thyroid cancer: molecular factors, management and treatment

Abstract: Medullary thyroid cancer (MTC) is an infrequent neuroendocrine tumor, which amounts to 3–5% of all thyroid malignancies. Approximately 75–80% of MTCs are sporadic neoplasms. The rest of 20–25% are familial cases that belong to multiple endocrine neoplasia (MEN) syndromes, specifically MEN2 and MEN3. These cases of familial MTC are attributed to an activating germline mutation of a tyrosine kinase receptor gene, the rearranged during transfection ( RET ) proto-oncogene, located on chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The primary technique cited by most of the papers and guidelines we found as the valid technique for initial treatment of MTC was total thyroidectomy (TT) combined with central compartment lymph node dissection (CCLND) [ 25 , 33 , 64 , 65 , 66 , 67 , 68 ]. The reason for choosing TT over hemithyroidectomy is the fact that multifocal and bilateral disease is present in most hereditary and 6% of sporadic MTC cases [ 5 , 62 ], and according to some sources, even in all hereditary and as many as 30% of sporadic MTC cases [ 7 ]. A slightly different approach was presented by a former Japanese researcher Miyauchi et al [ 69 ], who suggested that, among patients with sporadic MTC who lack mutations in the RET gene, the chance of bilateral primary lesions is close to 0%.…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The primary technique cited by most of the papers and guidelines we found as the valid technique for initial treatment of MTC was total thyroidectomy (TT) combined with central compartment lymph node dissection (CCLND) [ 25 , 33 , 64 , 65 , 66 , 67 , 68 ]. The reason for choosing TT over hemithyroidectomy is the fact that multifocal and bilateral disease is present in most hereditary and 6% of sporadic MTC cases [ 5 , 62 ], and according to some sources, even in all hereditary and as many as 30% of sporadic MTC cases [ 7 ]. A slightly different approach was presented by a former Japanese researcher Miyauchi et al [ 69 ], who suggested that, among patients with sporadic MTC who lack mutations in the RET gene, the chance of bilateral primary lesions is close to 0%.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Currently, lateral compartment lymph node dissection (LCLND) is the most controversial [ 5 , 7 , 25 , 33 , 64 , 65 , 72 , 73 ]. One view on deciding whether to perform prophylactic LCLND when there is no evidence of neck metastases on the US is based on the Ctn level [ 5 , 8 , 25 , 70 ].…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 3 more Smart Citations